Pengaruh Budaya Organisasi, Kepemimpinan, dan Human Capital terhadap Manajemen Perubahan dengan Gender sebagai Variabel Kontrol - Marlina, Yeni; Yulihasri (Jurnal Informatika Ekonomi Bisnis, 2024)
The decline in Indonesia's Global Innovation Index (GII) highlights the importance of fostering Change Management. In response, the government has initiated the Grand Design of Bureaucratic Reform, which emphasizes the importance of change management in achieving world-class governance. This study examines the influence of organizational culture, leadership, human capital, gender on change management at the Regional Civil Service Agency (BKD) of West Sumatra Province. The purpose of this study is to analyze the influence of Organizational Culture, Leadership, Human Capital, Gender on Change Management at the Regional Civil Service Agency of West Sumatra Province. In an era of globalization and rapid change, public sector organizations, face significant challenges in managing change to improve performance and service. This study aims to understand the extent to which organizational culture, leadership style, gender and human capital contribute to the success of change management. This study uses primary data obtained from respondents' answers in the form of filling out questionnaires via Google forms and direct questionnaire distribution. The data analysis technique uses the SEM-PLS method. The results of the study found that organizational culture has a positive and insignificant effect on change management at the Regional Personnel Agency of West Sumatra Province. Leadership has a positive and significant effect on change management at the Regional Personnel Agency of West Sumatra Province. Human capital has a positive and significant effect on change management at the Regional Personnel Agency of West Sumatra Province. Gender does not have a significant effect on change management at the Regional Personnel Agency of West Sumatra Province. The implications of these findings emphasize the importance of developing a supportive organizational culture, implementing an empowering and inspiring leadership style, and investing in employee competency development as key strategies to improve the effectiveness of change management in the public sector. This study provides valuable insights for practitioners and policy makers in designing appropriate interventions to strengthen change management in government organizations.